Approximate controllability of second-order non-autonomous stochastic impulsive differential systems. Issue 2 (29th July 2020) - Singh, Vikram; Chaudhary, Renu; Pandey, Dwijendra N.
Abstract: This paper is concerned with existence, uniqueness, and approximate controllability of mild solutions to second-order non-autonomous stochastic impulsive differential systems. The impulsive differential systems may provide mathematical models to the phenomena having discontinuous jumps. The main results are carried out by using the generalized Banach contraction principle, evolution family, and stochastic analysis. Finally, an example is given to illustrate the results.